Lingering illness or sudden death? Pre-exit employment developments in German establishments - Daniel Fackler; Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2012)
Using a large administrative dataset for Germany, this paper compares employment developments in exiting and surviving establishments. For both West and East Germany we find a clear shadow of death effect reflecting lingering illness: establishments shrink dramatically already several years before closure, employment growth rates differ strongly between exiting and surviving establishments, and this difference becomes stronger as exit approaches. We further show that prior to exit the workforce becomes on average more skilled, more female and older in exiting compared to surviving establishments. These effects are more clearly visible in West than in East Germany. Our results also hold when applying a matching approach.
Keywords: L2; D22; J65; 330; firm exits; shadow of death; Germany; Unternehmenserfolg; Liquidation; Beschäftigungseffekt; Schätzung; Deutschland